1994
DOI: 10.1007/bf00154311
|View full text |Cite
|
Sign up to set email alerts
|

Production of endo-1,4-?-glucanase and xylanase by Trichoderma reesei immobilized on polyurethane foam

Abstract: Endo-I,4-fI-glucanase and xylanase were produced by Trichodenna reesei immobilized on polyurethane foam using lactose as the main carbon source. The most porous carrier was found to be the best of those tested. The nitrogen source and KHzPO, concentration of the production medium had a marked effect on culture pH during the course of fermentation and, consequent&, on xylanase activity. An increase in lactose concentration from 7 to 27 gll resulted in an increase in endoglucanase activity (max. 730 VJml). xylan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 16 publications
2
8
0
3
Order By: Relevance
“…Gomes et al [25] also reported presence of organic nitrogen in the medium lead to increase in production of hydrolysing enzymes by T. aurantiacus. Moreover, it has also been reported that nitrogen can significantly affect the pH of the medium during the course of fermentation as reported by Haapala et al [26], thereby influences the microbial metabolism. Similar findings were reported by Deswal et al [3] and Jain et al [12].…”
Section: Effect Of Nitrogen Source and Its Concentrationmentioning
confidence: 79%
“…Gomes et al [25] also reported presence of organic nitrogen in the medium lead to increase in production of hydrolysing enzymes by T. aurantiacus. Moreover, it has also been reported that nitrogen can significantly affect the pH of the medium during the course of fermentation as reported by Haapala et al [26], thereby influences the microbial metabolism. Similar findings were reported by Deswal et al [3] and Jain et al [12].…”
Section: Effect Of Nitrogen Source and Its Concentrationmentioning
confidence: 79%
“…This reveals that ammonium nitrate plays an important role in growth of C. tropicalis and biodegradation of phenol. However, the decrease in phenol degradation at the concentration beyond level 2 can be attributed to the verity that higher concentration of nitrogen source significantly affects the pH of the medium during growth and also influences the microbial metabolism [39].…”
Section: Discussionmentioning
confidence: 99%
“…Òîìó ó äåÿêèõ гðèá³â, ÿê³ ðîñòóòü íà êñèëàí³, íå çàáðóäíåíîìó öåëþëîçîþ, ïðè íèçüêèõ ñï³ââ³äíîøåííÿõ àçîò/âóгëåöü â ñåðåäîâèù³ ìîжóòü ïðîäóêóâàòèñÿ êñèëàíîë³òè÷í³ фåðìåíòè, ÿê³ â³ëüí³ â³ä öåëþëàç. Îäíàê, âñòàíîâëåíî, ùî öåëþëîçîë³òè÷í³ ñóáñòðàòè º íåîáõ³äíèìè äëÿ ìàêñèìàëüíî¿ ïðîäóêö³¿ êñèëàíàçè Thermomonospora curvata [49] [26,36].…”
Section: продукція ксиланазиunclassified
“…MCIB 59 [16]. Нàéá³ëüø ïîâíî îõàðàêòåðèçîâàíî êñèëàíàçè Aspergillus fumigatus і Trichоderma reesei [3], ïðè÷îìó îñòàííÿ ïðîÿâëÿº ìàêñèìàëüíó ñåðåä гðèá³â àêòèâí³ñòü (3350 ÌΕìë -1 ) [26,36].…”
Section: продукція ксиланазиunclassified
See 1 more Smart Citation